Salivary N1-Methyl-2-Pyridone-5-Carboxamide, a Biomarker for Uranium Uptake, in Kuwaiti Children Exhibiting Exceptional Weight Gain - Goodson, Jo Max; Hardt, Markus; Hartman, Mor-Li; Alqaderi, Hend; Green, Daniel; Tavares, Mary; Mutawa, Al-Sabiha; Ariga, Jitendra; Soparkar, Pramod; Behbehani, Jawad; Behbehani, Kazem (Frontiers in Endocrinology, 2019)
In a longitudinal study of 6,158 Kuwaiti children, we selected 94 for salivary metabolomic analysis who had no initially measured evidence of metabolic disease. Half (43) remained healthy for two years. The other half (51) were selected because they became obese two years later. In the half becoming obese, a metabolomic analysis revealed that the level of salivary N1-Methyl-2-pyridone-5-carboxamide (2PY) had the highest positive association with obesity (p=0.0003, AUC=0.72) of 441 salivary biochemicals detected. 2PY is a recognized uremic toxin. Also, 2PY has been identified as a biomarker for uranium uptake. Considering that a relatively recent military conflict with documented uranium contamination of the area suggests that this weight gain could be a toxicological effect of long-time, low-level uranium ingestion. Comparison of salivary 2PY in samples from the USA and Kuwait found that only Kuwait samples were significantly related to obesity. Also, the geographic distribution of both reported soil radioactivity from 238U and measured salivary 2PY was highest in the area where military activity was highest. The prevalence pattern of adult diabetes in Kuwait suggests that a transient diabetogenic factor has been introduced into the Kuwaiti population. Although we did not measure uranium in our study, the presence of a salivary biomarker for uranium consumption suggests potential toxicity related to obesity in children.